Effects of cupping therapy on chronic musculoskeletal pain and collateral problems: a systematic review and meta-analysis - Tingting Sun; Yuanyuan Jia; Xiaosheng Dong; Yunlong Chai; Zhenmin Bai; Xiao Hou (BMJ Open)
Objectives Chronic musculoskeletal pain (CMP) is a prevalent and distressing condition. Cupping therapy, one of the most popular complementary and alternative medicines, has been widely used to reduce CMP. But the evidence remains controversial on the effect of cupping therapy on CMP. The objective of this review and meta-analysis is to assess the effectiveness of cupping therapy in patients with CMP.Design Systematic review and meta-analysis.Data sources PubMed, Web of Science, EBSCO, Cochrane Library and CNKI (China National Knowledge Infrastructure) were searched through 20 December 2024.Eligibility criteria for selecting studies We included randomised control trials that compared cupping therapy for patients with CMP on outcomes (ie, pain intensity, functional disability and mental health).Data extraction and synthesis Two independent reviewers used standardised methods to search, screen and code included studies. Risk of bias was assessed using the Cochrane Collaboration and Evidence Project tools. Meta-analysis was conducted using random and fixed effects models. Findings were summarised in GRADE (Grading of Recommendations Assessment, Development and Evaluation) evidence profiles.Results The results showed that cupping therapy (standardised mean difference (SMD)=−1.17; 95% CI=−1.93 to −0.42; p=0.002; I2=94%) had a significant reduction effect on patients with CMP’s pain intensity with moderate quality based on a random-effect model. But cupping therapy had no improvement effects on functional disability (SMD=−0.24; 95% CI=−0.93 to 0.46; p=0.51; I²=93%) and mental health (SMD=0.08; 95% CI=−0.12 to 0.27; p=0.46; I²=0%).Conclusions This study indicates that cupping therapy may be efficient in alleviating pain intensity in patients with CMP with immediate effects. But it cannot improve functional disability and mental health significantly.PROSPERO registration number CRD42023406219.